The refugees ebook - Nguyen, Viet Thanh (2023)
“Beautiful and heartrending” fiction set in Vietnam and America from the Pulitzer Prize–winning author of The Sympathizer (Joyce Carol Oates, The New Yorker ) In these powerful stories, written over a period of twenty years and set in both Vietnam and America, Viet Thanh Nguyen paints a vivid portrait of the experiences of people leading lives between two worlds, the adopted homeland and the country of birth. This incisive collection by the National Book Award finalist and celebrated author of The Committed gives voice to the hopes and expectations of people making life-changing decisions to leave one country for another, and the rifts in identity, loyalties, romantic relationships, and family that accompany relocation. From a young Vietnamese refugee who suffers profound culture shock when he comes to live with two gay men in San Francisco, to a woman whose husband is suffering from dementia and starts to confuse her with a former lover, to a girl living in Ho Chi Minh City whose older half-sister comes back from America having seemingly accomplished everything she never will, the stories are a captivating testament to the dreams and hardships of migration. “Terrific.” — Chicago Tribune “An important and incisive book.” — The Washington Post “An urgent, wonderful collection.” —NPR